PERFORMANCE OF ADMINISTRATIVE SERVICES IN THE DISDUKCAPIL CITY OF SAMARINDA - Subandi Subandi; Agus Sukristyanto (DIA: Jurnal Administrasi Publik, 2022)
The purpose of this study is to find out and describe the performance of administrative services in the Samarinda City Disdukcapil (Department of Population and Civil Registration) and find out and describe the supporting factors and inhibiting factors in the performance of administrative services in the Samarinda City Disdukcapil. Data were analyzed descriptively. The results showed that the performance of administrative services in the Samarinda City Population Office was known from several things. First, productivity, where every day there are always people who manage population administration in the Samarinda City Population Office. The Samarinda Disdukcapil is fully committed so that it completes the service in accordance with the existing tempo. The second is the quality of service where the Samarinda City Disdukcapil makes full efforts so that it provides quality services to the community. The population administration services of the Samarinda City Population Office are included in the great category of excellent. This is based on an assessment from the central government. The third is responsiveness, where the people of Samarinda City give a positive response to the administrative services in the Samarinda City Disdukcapil. Fourth, ressonability in which population administration services in the Samarinda City Population Office are carried out in accordance with the principles of public service consisting of transparency, accountability, conditional, participatory, equal rights, and a balance of rights and obligations. The fifth is accountability, where the population administration service in the Samarinda City Population Office refers to the Surat Keputusan Kepala Dinas Kependudukan dan Catatan Sipil Kota Samarinda Nomor: 470/13.b/100.16 concerning the Establishment of Service Standards on the Types of Services of the Samarinda City Population and Civil Registration Service. The policy is considered consistent.